PENGARUH CELEBRITY ENDORSER DAN ELECTRONIC WORD OF MOUTH TERHADAP REPURCHASE INTENTION YANG DIMEDIASI OLEH BRAND IMAGE RICHEESE NABATI YANG DIBELI SECARA ONLINE DI KOTA BANDUNG - Sinta Nursilawati; Hariyadi Triwahyu Putra (Universitas Pasundan, 2025)
This study aims to understand the impact of celebrity endorsers and electronic word of mouth on repurchase intention which is mediated by the Richeese Nabati brand image purchased online in Bandung City. The population in the study consists of millennial generation and generation Z individuals aged 17-30 years who have purchased Richeese Nabati products. The number of samples in this study amounted to 120 people. The research instrument has passed various test stages, namely validity test, reliability test, descriptive analysis, classical assumption test and multiple regression test. Research using SPSS version 25 software which is an analytical tool for testing data instruments and using a sobel calculator to conduct the sobel test. Brand Image is able to mediate the impact of celebrity endorsers and electronic word of mouth on repurchase intention.